BLUE OCEAN STRATEGY FORMULATION IN HOTEL INDUSTRY: The Case of Grage Ramayana Hotel - , Peter Ryan ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research intends to apply the blue ocean strategy in the context of hotel industry in Yogyakarta. Hotel industry currently experiences the intense competition, while competitors tend to face the competition by using the similar strategic profile (value curve) based on their star classification and pricing-policy. As the implication, the market segment is based on star classification